If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + 3(v + -7) = -28 Reorder the terms: -1 + 3(-7 + v) = -28 -1 + (-7 * 3 + v * 3) = -28 -1 + (-21 + 3v) = -28 Combine like terms: -1 + -21 = -22 -22 + 3v = -28 Solving -22 + 3v = -28 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + 3v = -28 + 22 Combine like terms: -22 + 22 = 0 0 + 3v = -28 + 22 3v = -28 + 22 Combine like terms: -28 + 22 = -6 3v = -6 Divide each side by '3'. v = -2 Simplifying v = -2
| 2x^2+22x+60=x | | 20y+13=15y-8 | | 4x+4x=64 | | (18a^3)-72a=0 | | z-0.45=5.97 | | 3a+(4b+2)I=9-6I | | 50+0.9*(y-30)=y | | -5x+24=-8(x-6)+6x | | -(-a)= | | 3x(4)=2 | | -n+n= | | 2(4z-2)-2(5-3z)=4 | | 5x+5=4x+4 | | 11+2(3n-11)=1 | | 6((2n^2)+3n-35)=0 | | (3x+4)-30=0 | | t-45=-48 | | 4x+8y-3x+2y= | | 1x+2y=18 | | 12+3(z-4)=-5z+5 | | -3(x+12)=16-x | | -6(n+3)+21=-3n-6 | | -2(2x+5)= | | 1x+2y+3z=18 | | (2x+13)=-81 | | 4(2x-6)= | | 17-13=2(x-6) | | 2u^2+2v^2+4=0 | | (2x-6)=28 | | 5(3c-1)-2=12c+2 | | -6x+12=2(3x-4) | | -2v-16=-8v+40 |